Intrasulcal Electrocorticography in Macaque Monkeys with Minimally Invasive Neurosurgical Protocols - Matsuo, Takeshi; Kawasaki, Keisuke; Osada, Takahiro; Sawahata, Hirohito; Suzuki, Takafumi; Shibata, Masahiro; Miyakawa, Naohisa; Nakahara, Kiyoshi; Iijima, Atsuhiko; Sato, Noboru; Kawai, Kensuke; Saito, Nobuhito; et al. (Frontiers in Systems Neuroscience, 2011)
Electrocorticography (ECoG), multichannel brain-surface recording and stimulation with probe electrode arrays, has become a potent methodology not only for clinical neurosurgery but also for basic neuroscience using animal models. The highly evolved primate’s brain has deep cerebral sulci, and both gyral and intrasulcal cortical regions have been implicated in important functional processes. However, direct experimental access is typically limited to gyral regions, since placing probes into sulci is difficult without damaging the surrounding tissues. Here we describe a novel methodology for intrasulcal ECoG in macaque monkeys. We designed and fabricated ultra-thin flexible probes for macaques with micro-electro-mechanical systems (MEMS) technology. We developed minimally invasive operative protocols to implant the probes by introducing cutting edge devices for human neurosurgery. To evaluate the feasibility of intrasulcal ECoG, we conducted electrophysiological recording and stimulation experiments. First, we inserted parts of the Parylene-C-based probe into the superior temporal sulcus to compare visually evoked ECoG responses from the ventral bank of the sulcus with those from the surface of the inferior temporal cortex. Analyses of power spectral density and signal-to-noise ratio revealed that the quality of the ECoG signal was comparable inside and outside of the sulcus. Histological examination revealed no obvious physical damage in the implanted areas. Second, we placed a modified silicone ECoG probe into the central sulcus and also on the surface of the precentral gyrus for stimulation. Thresholds for muscle twitching were significantly lower during intrasulcal stimulation compared to gyral stimulation. These results demonstrate the feasibility of intrasulcal ECoG in macaques. The novel methodology proposed here opens up a new frontier in neuroscience research, enabling the direct measurement and manipulation of electrical activity in the whole brain.